How long can tardigrades survive in the anhydrobiotic state? A search for tardigrade anhydrobiosis patterns. - Milena Roszkowska; Bartłomiej Gołdyn; Daria Wojciechowska; Zofia Księżkiewicz; Edyta Fiałkowska; Mateusz Pluskota; Hanna Kmita; Łukasz Kaczmarek (PLoS ONE)
Anhydrobiosis is a desiccation tolerance that denotes the ability to survive almost complete dehydration without sustaining damage. The knowledge on the survival capacity of various tardigrade species in anhydrobiosis is still very limited. Our research compares anhydrobiotic capacities of four tardigrade species from different genera, i.e. Echiniscus testudo, Paramacrobiotus experimentalis, Pseudohexapodibius degenerans and Macrobiotus pseudohufelandi, whose feeding behavior and occupied habitats are different. Additionally, in the case of Ech. testudo, we analyzed two populations: one urban and one from a natural habitat. The observed tardigrade species displayed clear differences in their anhydrobiotic capacity, which appear to be determined by the habitat rather than nutritional behavior of species sharing the same habitat type. The results also indicate that the longer the state of anhydrobiosis lasts, the more time the animals need to return to activity.